Optimalisasi Peran Penegak Hukum Dalam Menerapkan Pidana Kerja Sosial Dan Ganti Rugi Guna Mewujudkan Tujuan Pemidanaan Yang Berkeadilan - Sahat Maruli Tua Situmeang; Musa Darwin Pane; Wahyudi Wahyudi (Fakultas Hukum Universitas Islam Indonesia, 2020)
This study aims to determine the obstacles in implementing social work sanction and compensation by law enforcers and the efforts that must be undertaken in order to achieve the objective of fair punishment. The approach method in this research is a sociological juridical approach. The research specifically used analytical descriptive method. The results of this study conclude that social work criminal sanction have not been implemented by law enforcers, this is because there is no clear regulation in the form of legislation as the legal basis, including the absence of an institution that functions to oversee the implementation of social work sanctiion and compensation. As for the efforts aside of the support for the establishment of laws and regulations so that social work sanction can be applied, is also by the courage of law enforcers to implement social work sanction, so that the objectives of fair punishment can be realized.